Perioperative venous thromboembolic disease and the emerging role of the novel oral anticoagulants: An analysis of the implications for perioperative management - Mookadam, Martina (Ann Card Anaesth, 2015)
Venous thromboembolism includes 2 inter-related conditions: Deep venous thrombosis and pulmonary embolism. Heparin and low-molecular-weight heparin followed by oral anticoagulation with vitamin K agonists is the first line and current accepted standard therapy with good efficacy. However, this therapeutic strategy has many limitations including the significant risk of bleeding and drug, food and disease interactions that require frequent monitoring. Dabigatran, rivaroxaban, apixaban, and edoxaban are the novel oral anticoagulants that are available for use in stroke prevention in atrial fibrillation and for the treatment and prevention of venous thromboembolism (HYPERLINKł ”1). Recent prospective randomized trials comparing the NOACs with warfarin have shown similar efficacy between the treatment strategies but fewer bleeding episodes with the NOACs. This paper presents an evidence-based review describing the efficacy and safety of the new anticoagulants compared to warfarin.